Pengaruh Stres Kerja dan Psychological Capital Terhadap Kinerja Karyawan dan Turnover Intention - Ariana Putri; Antin Rakhmawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
In the modern work era full of pressure and high targets, work stress becomes a significant factor that affects performance and increases employee turnover intention. This study aims to analyze the effect of work stress and psychological capital on employee performance and turnover intention, including the mediating role of performance in the relationship. The study was conducted at PT Universal Eco Lestari, Pasuruan, with a quantitative correlational approach to 86 respondents. The results showed that work stress had a negative effect on performance and a positive effect on turnover intention, while psychological capital had a positive effect on performance and a negative effect on turnover intention. However, employee performance did not mediate the relationship between psychological capital and turnover intention. Overall, the regression model was significant and met statistical assumptions. These findings emphasize the importance of stress management and strengthening psychological capital in efforts to improve performance while reducing employee intentions to leave the organization.